Comparação de parâmetros radiográficos e tomográficos para determinação da acurácia e da confiabilidade na predição de dificuldade de terceiros molares mandibulares - Santos, Thiago Jonathan Silva dos (2024)
Lower third molar extraction (3MIs) is a common procedure in Dentistry. During surgical planning, the variability of clinical and imaging presentations related to these teeth must be considered, which may predict greater difficulty. operation, such as inclination, degree of tooth inclusion, among others. With this, the surgical plan strategies aided by the analysis of panoramic radiographs (RP) or Cone beam computed tomography (CBCT) should be increasingly reliable for the real prediction of difficulty in carrying out the procedure. The purpose of the present work was to compare different imaging parameters in predicting the degree of difficulty surgery involving the removal of 3MIs. A cross-sectional, retrospective study was carried out, with PR and TCFC obtained consecutively between the years 2018 and 2023, in the imaging of the undergraduate dentistry course at the Federal University of Ceará – Sobral campus. The study followed the guidelines of the STROBE initiative. The final sample consisted in 52 pairs of images (RP and CBCT), analyzed using CorelDRAW software ® (analysis two-dimensional) and 3D Slicer (three-dimensional analysis) considering the following parameters: Pell and Gregory classification, Winter classification, dental bulbosity, proximity to the inferior alveolar canal and assessment of marginal bone loss. The analyzes were carried out with the aid of two software: CorelDRAW® for measurements in RP, and 3D SLICER for measurements in CBCT. The results demonstrated that PR in some classifications generated evaluation discrepancies when compared with computed tomography scans. These diagnostic discrepancies between these exams prove that PR can generate errors in predicting difficulty at the time of pre-surgical planning of tooth extractions 3MIs. Statistical analysis included McNemar tests, calculation of the coefficient of agreement, and assessment of sensitivity, specificity, positive and negative predictive values, and accuracy. The research showed statistically significant differences between RP and CBCT in the evaluation of 3MIs, especially in the vicinity of the inferior alveolar nerve canal, where the RPs showed high sensitivity (93.9%) but low specificity (0%). In the classification of Pell and Gregory, the PRs had a sensitivity of 87.5% and a specificity of 61.1% (p=0.004). A Winter classification revealed low sensitivity for vertical teeth, contrasting with high specificity. These findings highlight the importance of CBCT for a more accurate assessment precise anatomy and surgical complexity, pointing to the limitations of RPs in specific surgical planning contexts, with the Pell and Gregory classification showing significant differences in sensitivity and specificity for bi- and three-dimensional.